2017
DOI: 10.1080/15563650.2017.1327067
|View full text |Cite
|
Sign up to set email alerts
|

Sticky situations: cyanoacrylate exposures reported to a poison control system

Abstract: In this case series, the majority of cases occurred in children and most exposures did not result in significant morbidity. Notably, there was wide variation in terms of recommended treatments; further study is needed to determine the optimal treatment method and to standardize poison center recommendations for treating patients with cyanoacrylate exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…To our knowledge, this is the first study comparing various suggested methods. A recent study by Carstairs et al 10 showed that there was a very wide variation of recommended treatments given by poison control centres to callers. Our review also shows a broad range of proposed interventions but no comparisons done to date.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study comparing various suggested methods. A recent study by Carstairs et al 10 showed that there was a very wide variation of recommended treatments given by poison control centres to callers. Our review also shows a broad range of proposed interventions but no comparisons done to date.…”
Section: Discussionmentioning
confidence: 99%
“…In the instance of low quality data, the possible risks become more important. While some of these risks are discussed by the authors, they include wound contamination if appropriate wound cleaning does not occur, exothermic reaction potentially leading to burns, irritant effects, poor cosmetic outcome for large or poorly closed wounds, damage to underlying structures for deep wounds on inappropriate application, and inadvertent self-adhesion to unintended objects (Carstairs et al, 2017;Eyth, Echlin, & Jones, 2016;Kelemen, Karagergou, Jones, & Morritt, 2016). A recent 10-year review of cyanoacrylate exposures reported to a single US regional poison control center found 893 reports of accidental and intentional exposures, of which over 26% required management in a healthcare facility.…”
mentioning
confidence: 99%
“…A recent 10-year review of cyanoacrylate exposures reported to a single US regional poison control center found 893 reports of accidental and intentional exposures, of which over 26% required management in a healthcare facility. While most of the effects were minor, just under 9% suffered moderate effects from exposure (Carstairs et al, 2017). Commercial cyanoacrylates are not designed for medical use.…”
mentioning
confidence: 99%